Efektivitas model LC 7E dengan metode TSTS terhadap kemampuan berpikir kritis dan minat belajar peserta didik - Zahra, Sayidatul Maghfiroh Az; Suparni (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2024)
The purpose of this study is to evaluate the efficacy of the learning cycle. 7E (LC 7E), LC 7E with TSTS method, and conventional method of learning on critical thinking skills and interest in learning. The type of research is quantitative with the research design is nonequivalent control group design. The independent variables are LC 7E and LC 7E with the TSTS method. The dependent variables are critical thinking ability and interest in learning. The population are VII grade students at MTs Negeri 9 Bantul and the samples are class VII C, VII B, and VII A. The research instruments used were data collection instruments in the form of critical thinking ability tests and learning interest scales as well as learning instruments in the form of learning modules dan LKPD. The data analysis used for critical thinking ability data is Kruskall Wallis test while for learning interest data is One Way Test Anova test and followed by Scheffe Test. The research results show that in terms of critical thinking abilities (1) LC 7E is no more effective than the conventional model, (2) the LC 7E with the TSTS method is no more effective than the conventional model, and (3) the LC 7E with the TSTS method is no more effective than the LC 7E. Meanwhile, in terms of interest of learning shows that (4) Learning C 7E is more effective than the conventional model, (5) LC 7E model with the TSTS method is more effective than the conventional model, and (6) the Learing Cycle 7E with the TSTS method is not more effective than the LC  7E.